Analisis implementasi keterbukaan infomasi publik berbasis electronic government di Desa Kedungsumber, Kecamatan Temayang, Kabupaten Bojonegoro (Integritas : Jurnal Antikorupsi, 2023)
The disclosure of public information becomes one of the important elements for the realization of Good Governance in the administration of government. One of the villages in East Java that have implemented electronic-based public information disclosure and became the top 10 in the village competition with national-level public disclosure is Kedungsumber Village. Remembering this so that village government can be held transparently, participative, and accountable. The type of research used in this study is descriptive research, with a qualitative approach to case studies. Data analysis used interactive models from Miles, Huberman, and Saldana. The results of this study show that the implementation of E-Government-based Public Information Disclosure/ Keterbukaan Informasi Publik (KIP) in Kedungsumber Village has been carried out. However, there are several shortcomings, namely that the task is still heavily burdened by the secretary of the Information and Documentation Management Officer/ Pejabat Pengelola Informasi dan Dokumentasi (PPID), the absence of SOPs related to the publication of KIP, the difficulty of signals in the village becomes a constraint in communication, there is no improvement and development of Human Resources in PPID. The process of mitigating E-Government risks is still very minimal. As for the information that must be announced periodically, immediately, and available at any time has been provided and published, but PPID Kedungsumber Village in the process of KIP has not tested the consequences, and the level of application of E-government Kedungsumber Village is Enhanced.